Correlation between Femoral Head Lateralization and Bone Morphology in Primary Hip Osteoarthritis - Kenta Inagaki; Shigeo Hagiwara; Yuya Kawarai; Hiroakira Terakawa; Shuichi Miyamoto; Chiho Suzuki; Hiroyuki Yamagata; Junichi Nakamura; Seiji Ohtori; Satoshi Iida (Advances in Orthopedics, 2023)
Background. Osteoarthritis (OA) is the most common disease of the hip in adults, and its etiology is divided into two groups: primary and secondary. Although acetabular dysplasia is the most frequent reason for total hip arthroplasty (THA) in Japan, primary OA has increased recently. Although there are two types of femoral head migration in primary OA: superior and medial, there are some patients with prominent femoral head lateralization. This study aimed at evaluating the relationship between femoral head lateralization and bone morphology of the acetabulum and proximal femur using radiographic factors in primary OA of the hip. Methods. A retrospective study was conducted between 2008 and 2017 to assess 1308 hips with OA who underwent primary THAs at our institute. The diagnostic criteria for primary OA were Crowe type 1, Sharp’s angle <45°, and center-edge (CE) angle >25°. We classified patients with primary OA into two groups based on femoral head lateralization: group L with lateralization or group N without. Radiographic factors included Sharp’s angle, CE angle, acetabular inclination, acetabular depth ratio (ADR), acetabular head index (AHI), and femoral neck-shaft angle (FNA), all examined on an anteroposterior pelvic radiograph. Femoral neck anteversion was calculated using computerized axial tomography. Results. Primary OA was diagnosed in 210/1308 hips (16.1%) (group L: 112 hips (8.6%); group N: 98 (7.5%)). Patient demographics were not significantly different. Radiographic factors with observed significant differences between group L and group N were the average CE angle (33.0° vs. 35.1°, respectively, p = 0.009), ADR (251.6 vs. 273.4, p < 0.001), AHI (77.2 vs. 80.4, p < 0.001), and FNA (136.9° vs. 134.8°, p = 0.012). Conclusions. This investigation suggests that primary OA with femoral head lateralization demonstrated specific identifiable radiographic characteristics in the acetabulum and proximal femur that might contribute to hip joint instability such as the dysplastic hip.